2018
DOI: 10.1111/cdev.13194
|View full text |Cite
|
Sign up to set email alerts
|

Dyscalculia and Typical Math Achievement Are Associated With Individual Differences in Number‐Specific Executive Function

Abstract: Deficits in numerical magnitude perception characterize the mathematics learning disability developmental dyscalculia (DD), but recent studies suggest the relation stems from inhibitory control demands from incongruent visual cues in the nonsymbolic number comparison task. This study investigated the relation among magnitude perception during differing congruency conditions, executive function, and mathematics achievement measured longitudinally in children (n = 448) from ages 4 to 13. This relation was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 99 publications
4
39
1
4
Order By: Relevance
“…124 Also, in a large-scale study of middle school children, number comparison performance during incongruent trials of the task continued to predict math achievement after controlling for several components of executive function, including inhibitory control. 123 Similar findings have also been reported in adults. 125 Further, using the same stimulus control method as DeWind et al, 84 Starr et al 126 measured the relative weight placed on numerical and nonnumerical stimulus features in the number comparison task and showed that, in children, number sense was a stronger predictor of math achievement than either nonnumerical bias measured in the comparison task or inhibitory control measured in an independent task.…”
Section: Challenge 3: Measures Of Number Sense Are Not Measuring Numbsupporting
confidence: 77%
See 3 more Smart Citations
“…124 Also, in a large-scale study of middle school children, number comparison performance during incongruent trials of the task continued to predict math achievement after controlling for several components of executive function, including inhibitory control. 123 Similar findings have also been reported in adults. 125 Further, using the same stimulus control method as DeWind et al, 84 Starr et al 126 measured the relative weight placed on numerical and nonnumerical stimulus features in the number comparison task and showed that, in children, number sense was a stronger predictor of math achievement than either nonnumerical bias measured in the comparison task or inhibitory control measured in an independent task.…”
Section: Challenge 3: Measures Of Number Sense Are Not Measuring Numbsupporting
confidence: 77%
“…For example, in a study of young children, number comparison performance predicted math in two separate experiments using different inhibitory control tasks for each . Also, in a large‐scale study of middle school children, number comparison performance during incongruent trials of the task continued to predict math achievement after controlling for several components of executive function, including inhibitory control . Similar findings have also been reported in adults .…”
Section: Challenge 3: Measures Of Number Sense Are Not Measuring Numbsupporting
confidence: 58%
See 2 more Smart Citations
“…While earlier behavioral research suggested that the precision of numerical representation is predictive of formal arithmetic and gets refined with development and mathematical learning (Halberda and Feigenson, 2008; Nys et al, 2013; Piazza, 2010; Piazza et al, 2010; Piazza et al, 2013), other recent evidence has led to a slightly different view: what might be changing with development and mathematical competence could be the ability to focus on numerical information while filtering out non-numerical dimensions during a numerical comparison task (Castaldi et al, 2018; Piazza et al, 2018; Starr et al, 2017; Wilkey et al, 2018). The influence of non-numerical dimensions on numerical judgments decreases over normotypical development and both dyscalculic children (Bugden and Ansari, 2016; Piazza et al, 2018; Szucs et al, 2013; Wilkey et al, 2018) and adults (Castaldi et al, 2018) seem to be disproportionately affected by non-numerical dimensions during numerical comparison tasks. In light of these behavioral findings, it would be interesting to see whether in dyscalculic subjects, numerical information at the neuronal level is less precisely encoded overall or merely less accessible to attentional selection.…”
Section: Discussionmentioning
confidence: 99%